Electronic Devices to Investigate Offences of Torturing, Abusing, Molesting, Assaulting or Killing the Innocent Children: Aftab Ahmad Malik - Malik, Aftab Ahmad (International Journal for Electronic Crime Investigation, 2019)
The offences of torturing, abusing, molesting, assaulting, physical torturing or killing the innocent children are increasing day by day in our society. Mostly such offences are practiced on the young learners studying in various institutions ranging from lower primary, primary and middle level. Irrespective of the privately managed or public institution, the heinous offences occur in the schools. The torture ratio is comparatively high in village schools and also where the learners are sent exclusively for religious education. In such schools mostly the poor and orphan learners are admitted and may be the whole time resident of the schools. Another common aspect is the torture extended to innocent young female or male, who are resident servants. There are also periodical reports of inflicting torture sometime accompanied by killing. Another category of offenders is that who choose the innocent children from local neighbouring localities rape, molest, sodomise and then kill them. They either committheoffencesaloneorwiththeirgangorallies. Incaseofkillingthedeadbodyisthrowninthe locality or nearby canal. The procedure or steps taken by offender for committing an offence is “Modus Operandi”. On most of the occasions the forensic evidence left and available by means of which the criminals can be traced, while in certain other cases, it is not adequate for the purpose of prosecution. A few case study are revealed. In this paper, we focus on some effective digital and electronic devices to facilitate the investigation to collect effective evidence usable in the court of law. The relevant tools for retrieving the forensic data are also introduced..